Preliminary Results Suggest Tranexamic Acid is Safe and Effective in Arthroplasty Patients with Severe Comorbidities - Whiting, Daniel R. (Springer US, 2013)
BACKGROUND: Tranexamic acid (TXA) reduces blood loss and transfusion after total joint arthroplasty (TJA) but concerns remain that patients with severe medical comorbidities might be at increased risk for thromboembolic complications. QUESTIONS/PURPOSES: Among patients undergoing primary TJA with severe systemic medical disease, (1) was TXA associated with increased symptomatic thromboembolic events; (2) was TXA associated with decreased blood transfusion rates; and (3) were there differences in symptomatic thromboembolism or transfusions in the subset of patients with a history of, or risk factors for; thromboembolic disease? METHODS: We performed a retrospective review of 1131 primary TJAs in 1002 patients with American Society of Anesthesiologists score III or IV. Of these, 402 had at least one of seven risk factors for thromboembolic events and were designated as high risk; 240 of those patients received TXA. Outcome measures included 30-day postoperative symptomatic thromboembolic events and postoperative transfusion. RESULTS: There were no differences in symptomatic thromboembolic events within 30 days of surgery between patients who received TXA and those who did not (2.5% versus 2.6%, p = 0.97). Fewer patients treated with TXA received transfusions (11% with versus 41% without; p < 0.0001). In high-risk patients, TXA was not associated with an increase in symptomatic thromboembolic events (6.7% with versus 4.3% without; p = 0.27) and was associated with a decrease in transfusion rates (17% with versus 48% without; p = 0.001). CONCLUSIONS: Although TXA seemed safe and effective in this database review of patients with severe medical comorbidities, a larger prospective trial is warranted to confirm these results. LEVEL OF EVIDENCE: Level III, therapeutic study. See Guidelines for Authors for a complete description of levels of evidence.